Dating prograde amphibolite and granulite facies metamorphism using in situ monazite U-Pb SHRIMP analysis - Forbes, C.; Giles, D.; Betts, P.; Weinberg, R.; Kinny, Peter (University of Chicago Press, 2007)
In situ SHRIMP U-Pb analysis of monazite grains from pelites within an early-formed high-temperature shear zonein the southern Broken Hill Block, Australia, has been used to constrain the timing of prograde amphibolite faciesand peak granulite facies metamorphism within the terrain. Geochronological analyses from grains inhabiting texturallydistinct localities revealed two distinct age populations, ca. 1619 and ~1600 Ma. The older age was obtainedfrom grains that occur as inclusions completely enclosed within coarse-grained K-feldspar and garnet grains, whichevidently armored the monazite inclusions against resetting during younger deformation and metamorphic events.The ca. 1619-Ma monazite population occurs as part of an amphibolite facies inclusion assemblage hosted withinthe peak granulite facies mineral assemblage and constrains the timing of prograde amphibolite facies metamorphismwithin the Broken Hill Block. The younger ~1600-Ma monazite age population was from grains within the pervasiveshear fabric of the pelites or adjacent to fractures or grain boundaries in the matrix. The ~1600-Ma age populationrepresents either a later stage of monazite growth or isotopic resetting during deformation along the high-temperatureshear zone at peak granulite facies conditions.